COMPLICATIONS AFTER EXTRACTION OF IMPACTED THIRD MOLARS - LITERATURE REVIEW - Elitsa G. Deliverska; Milena Petkova (Peytchinski Publishing, 2016)
Third molar surgery is the most common procedure performed by oral and maxillofacial surgeons worldwide. This article addresses the incidence of specific complications and, where possible, offers a preventive or management strategy. Complications, such as pain, dry socket, swelling, paresthesia of the lingual or inferior alveolar nerve, bleeding, and infection are most common. Factors thought to influence the incidence of complications after third molar removal include age, gender, medical history, oral contraceptives, presence of pericoronitis, poor oral hygiene, smoking, type of impaction, relationship of third molar to the inferior alveolar nerve, surgical time, surgical technique, surgeon experience, use of perioperative antibiotics, use of topical antiseptics, use of intra-socket medications, and anaesthetic technique. For the general dental practitioner, as well as the oral and maxillofacial surgeon, it is important to be familiar with all the possible complications after this procedure. This improves patient education and leads to prevention, early recognition and management.